Chance-Based Just-World Beliefs and Internet Altruistic Behavior among University Students - Rini Hartati; Nasywa Hafizah; Ade Irma Putri Magdalena; Marlin Sianturi (CV. Era Digital Nusantara, 2026)
The rapid development of digital technology and social media has increased university students’ engagement in Internet Altruistic Behavior (IAB). One psychological factor associated with this behavior is Belief in a Just World (BJW), particularly the chance dimension, which reflects the belief that life events are influenced by luck, fate, and random circumstances. This study aimed to examine the association between the chance dimension of BJW and Internet Altruistic Behavior among university students. A cross-sectional correlational study was conducted involving 353 university students in Riau Province selected through a cluster sampling procedure. Data were collected using the Belief in a Just World Scale and the Internet Altruistic Behavior Scale and analyzed using simple linear regression. The results showed that the chance dimension of BJW was positively associated with Internet Altruistic Behavior (R = .359, R² = .129, p < .001), indicating that the model explained 12.9% of the variance in Internet Altruistic Behavior. These findings provide preliminary evidence that the chance dimension, as one of the source-specific dimensions of Belief in a Just World, is associated with prosocial behavior in digital environments among university students.